Primary mesenchymal tumors of the colon: A report of three cases - Yaren, Arzu; Değirmencioğlu, Serkan; Demirkan, Neşe Çallı; Demiray, Atike Gökçen; Taşköylü, Burcu; Gököz Doğu, Gamze (Turkish Journal of Gastroenterology, 2014)
Abstract Primary mesenchymal tumors of the colon are extremely rare tumors among soft tissue sarcomas. These tumors are more aggressive and have poorer prognosis than adenocarcinoma of the colon. Here, we presented 3 cases of primary mesenchymal tumors of the colon. Their histopathological diagnoses are leiomyosarcoma, pleomorphic liposarcoma, and desmoplastic small round cell tumor, respectively. The rarity of primary mesenchymal tumors of the colon makes it difficult to approach the treatment and predict the prognosis of these rare tumors.